18F-Fluorodeoxyglucose Positron Emission Tomography Predicts Treatment Efficacy and Clinical Outcome for Patients With Pancreatic Carcinoma: A Meta-analysis. Issue 8 (September 2019) - Wang, Li; Dong, Ping; Shen, Guohua; Hou, Shengzhong; Zhang, Yi; Liu, Xubao; Tian, Bole
Abstract : Objectives: 18 F-Fluorodeoxyglucose positron emission tomography (FDG-PET) has been an important modality for detecting malignancies. Recently, an increasing number of studies reported the utility of FDG-PET parameters in predicting clinical outcomes and treatment assessment in variety of cancers. We aimed at clarifying both the prognostic role and assessment value of FDG-PET in pancreatic carcinoma. Methods: We systematically searched electronic databases of PubMed, Embase, Cochrane Library, and Web of Science to identify relevant studies to conduct this meta-analysis. Comparative analyses of the pooled hazard ratio (HR) for overall survival were performed to assess the utility of FDG-PET parameters in prognosis evaluation and treatment assessment by random-effect model. Results: Twenty-three studies with 1762 patients met the inclusion criteria of this meta-analysis. The pooled results revealed that greater maximum standardized uptake value of the primary tumor was significantly correlated with poorer overall survival (HR, 1.31; 95% confidence interval, 1.15–1.50; P < 0.001). Besides, greater reduction of maximum standardized uptake value after treatments indicated significant better overall survival (HR, 0.68; 95% confidence interval, 0.47–0.98; P = 0.037). Conclusions: 18 F-Fluorodeoxyglucose positron emission tomography parameters might be helpful not only for predicting survival outcome but also for selecting potentially efficacious treatments in patients with pancreatic carcinoma.